CRITICAL REVIEW ON EFFICIENT METHODS UTILIZED IN TREATING ACNE AMONG TEENAGERS. - 1Sultan Alfateih, 2Hamad HadiJahairAlfataih, 3Said saidanmisfer Al-fataih, 4Abdullah Falah abdulllahAlyami, 5Saleh Ali Saad Alyami, 6Salem Mohammed Mahdi, 7Ali Hamdan Fahad Al fahad, Mana Salem Mohmmad Alrobie (Chelonian Research Foundation, 2022)
Acne could be skin infections that regularly cause torment among young people and influence them. This precise audit aims to assess the adequacy of different acne medications teenagers. This critical review begins by describing the significance of tending to skin break in this population and, afterward, gives a rundown of the most recent progress in acne treatment. The rules outline the criteria for selecting what to think about and the strategies to audit them. The discoveries are displayed through pictures, tables, and charts, which indicate the adequacy of distinctive medicines. The discussion area fundamentally assesses the discoveries and recognizes crevices in existing inquiries. The determination summarizes the most points and offers proposals for specialists and policymakers to make strides in teen acne administration. Keywords: Acne, teenagers, Treatment, Efficiency, Dermatology